Development of a new nanobiotechnology method for the differential diagnosis of ocular adnexal tumors - S.V. Saakyan; D.A. Skladnev; A.P. Alekseeva; O.V. Beznos; V.V. Sorokin (РМЖ "Клиническая офтальмология")
S.V. Saakyan1, D.A. Skladnev2, A.P. Alekseeva1, O.V. Beznos1, V.V. Sorokin2 1Helmholtz National Medical Research Center, Moscow, Russian Federation 2Federal Research Center "Fundamental Basis of Biotechnology", Moscow, Russian Federation Aim: to develop a new nanobiotechnology method for the differential diagnosis of ocular adnexal tumors. Patients and Methods: 192 eyelid or conjunctival tumor samples from 192 patients were examined. Controls were healthy tissue samples from the same eye. To register and obtain significant differences in the generation of biogenic silver nanoparticles in situ, the key parameters of the reaction of the reduction of silver cations were selected and optimized. To generate de novo biogenic silver nanoparticles, tissue samples were placed in a sterile solution of a cation source in aseptic conditions. Nanoparticles were generated in situ using a sterile solution of Tollens' reagent (Ag(HN3)2NO3). Results: the optimal parameters of a new nanobiotechnology method were established to conduct the reduction reaction to generate biogenic silver nanoparticles. The required concentration of Tollens' reagent (source of cations) was 63 μg/ml. The wavelength used to observe the de novo generation of biogenic silver nanoparticles (λ) was 410 nm. Obtaining the most significant changes in the optical density of the reaction mixture with biogenic nanoparticles required 10 to 20 min, although the first changes were documented starting from the 5th minute of the reduction reaction. Benign and malignant tumors are characterized by different metabolic activities, i.e., benign eyelid and conjunctival tumors reduce cations more slowly than malignant tumors. The parameters of reducibility of benign ocular adnexal tumors did not significantly differ depending on tumor location and type. Among the malignant conjunctival tumors, melanoma is characterized by the highest reducibility p<0.05). Among the malignant eyelid tumors, no significant differences were found for different tumor types. Conclusions: this novel nanobiotechnology method provides a differential diagnosis of benign and malignant ocular adnexal tumors. The practical relevance of this method lies in differentiating benign and malignant tumors to schedule management strategies and surgical interventions. Keywords: tumor, eyelids, conjunctiva, silver nanoparticles, biogenic synthesis, express diagnostics, ocular oncology. For citation: Saakyan S.V., Skladnev D.A., Alekseeva A.P., Beznos O.V., Sorokin V.V. Development of a new nanobiotechnology method for the differential diagnosis of ocular adnexal tumors. Russian Journal of Clinical Ophthalmology. 2024;24(1):25–29 (in Russ.). DOI: 10.32364/2311-7729-2024-24-1-5.